Spacetime and geometry : an introduction to general relativity - Carroll, Sean M. (Cambridge: Cambridge University Press, 2021)
"Spacetime and Geometry is an introductory textbook on general relativity, specifically aimed at students. Using a lucid style, Carroll first covers the foundations of the theory and mathematical formalism, providing an approachable introduction to what can often be an intimidating subject. Three major applications of general relativity are then discussed: black holes, perturbation theory and gravitational waves, and cosmology. Students will learn the origin of how spacetime curves (the Einstein equation) and how matter moves through it (the geodesic equation). They will learn what black holes really are, how gravitational waves are generated and detected, and the modern view of the expansion of the universe. A brief introduction to quantum field theory in curved spacetime is also included. A student familiar with this book will be ready to tackle research-level problems in gravitational physics"--
This book was previously published by Pearson Education, Inc. and reissued by Cambridge University Press 2019.
Includes bibliographical references and index.
Keywords: General relativity (Physics)